Land Acquisition Of Toll Roads For Public Interest In The Kendal District - Mahyuni Mahyuni; Pradikta Andi Alvat; Anis Mashdurohatun (Jurnal Akta, 2019)
The purpose of this study was to: 1) determine the procurement of land for public purposes on a motorway in Kendal. 2) Knowing the Notary PPAT role in proving the juridical data on compensation for land acquisition. 3) To analyze the challenges and solutions implementation of land acquisition for public use on the highway in Kendal. The method used is a socio-legal approach. Socio-legal is an approach taken by seeing something legal reality in society, and is an approach that is used to look at the legal aspects of social interaction in the community.Based on data analysis concluded that: 1) the implementation of land acquisition for public purposes toll on the motorway in Kendal includes 4 stages of land acquisition planning phase, preparation phase by forming a team preparation, the implementation phase of land acquisition, and the outcome of the submission phase. 2) The role of the Notary / PPAT of completing related legal compensation and transfer of land rights. 3) The obstacles that occur freely buying and selling land, the process of inheritance, their absentee land ownership, does not agree with the price offered. The solution that the government should provide compensation based on the value of compensation, so that it can realize a fair society, and prosperous.Keywords: Land Acquisition; Torts; Highway.